2019
DOI: 10.1007/s13311-019-00770-z
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 Induced the β-Amyloid Protein Deposition and Neuronal Apoptosis Via Upregulating the Synthesis of Prostaglandin E2 and 15-Deoxy-Δ12,14-prostaglandin J2

Abstract: Elevated levels of cyclooxygenase-2 (COX-2) and prostaglandins (PGs) have been shown to be involved in the pathogenesis of Alzheimer's disease. Analysis of the underlying mechanisms elucidated a function of sequential PGE 2 and PGD 2 synthesis in regulating β-amyloid protein (Aβ) deposition by modulating tumor necrosis factor α (TNF-α)-dependent presenilin (PS)1/2 activity in COX-2 and APP/PS1 crossed mice. Specifically, COX-2 overexpression accelerates the expression of microsomal PGE synthase-1 (mPGES-1) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 66 publications
2
19
0
Order By: Relevance
“…With regard to the effects of COX‐2/PGE2 on apoptosis, overexpression of COX‐2/PGE2 could promote apoptosis in several types of cells. 26 , 27 , 28 , 29 , 30 , 31 The impacts of COX‐2 inhibitors on apoptosis of cells in vitro are dependent on their doses. The high concentration of celecoxib (50‐100 mmol/L) may increase their apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the effects of COX‐2/PGE2 on apoptosis, overexpression of COX‐2/PGE2 could promote apoptosis in several types of cells. 26 , 27 , 28 , 29 , 30 , 31 The impacts of COX‐2 inhibitors on apoptosis of cells in vitro are dependent on their doses. The high concentration of celecoxib (50‐100 mmol/L) may increase their apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The results of Morris water maze and nest construction experiments demonstrated that COX-2 overexpression exacerbated cognitive decline in 6-month-old APP/PS1 mice. 12 In addition, COX-2 expression in APP/PS1 Tg mice appeared with the early onset of APs burden in the cerebral cortex and hippocampus of 6month-old APP/PS1 Tg mice. 12 More interestingly, we double stained the cerebellum, medulla oblongata, and spinal cord of 6month-old COX-2/APP/PS1 Tg mice with Aβ and COX-2.…”
mentioning
confidence: 94%
“…12 In addition, COX-2 expression in APP/PS1 Tg mice appeared with the early onset of APs burden in the cerebral cortex and hippocampus of 6month-old APP/PS1 Tg mice. 12 More interestingly, we double stained the cerebellum, medulla oblongata, and spinal cord of 6month-old COX-2/APP/PS1 Tg mice with Aβ and COX-2. The results demonstrated that APs appeared in the cerebellum but not in the medulla oblongata or spinal cord of 6-month-old COX-2/ APP/PS1 Tg mice (Fig.…”
mentioning
confidence: 94%
“…As an important synthases of PGs, the activation of COX-2 will inevitably affect the metabolism of PGs. The over accumulation of PGE 2 in the brain can activate presenilin (PS) 1/2 by upregulating tumor necrosis factor (TNF)-α, leading to promote the production and aggregation of Aβ and ultimately damage the learning and memory ability of APP/PS1 Tg mice (9). PGI 2 promotes the amyloid metabolism of amyloid precursor protein (APP) by activating APH-1α and − 1β and increases the production and deposition of Aβ, which impaired the learning and memory ability of AD mice (10).…”
Section: Introductionmentioning
confidence: 99%
“…As the self dehydrating product of PGD 2 , 15-deoxy-Δ 12,14 -PGJ 2 (15d-PGJ 2 ) also showed inhibition on the activity of APH-1α/1β and PS1 (11). More interestingly, only high concentration of 15d-PGJ 2 can inhibit the activity of γ-secretase, while low concentration of 15d-PGJ 2 activates PS1 and PS2 (9). However, the questions are easily raised why 15d-PGJ 2 played different biological functions from other PGs in AD.…”
Section: Introductionmentioning
confidence: 99%